1990
DOI: 10.1073/pnas.87.8.3195
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical localization of the alpha subspecies of protein kinase C in rat brain.

Abstract: The distribution ofthe a subspecies ofprotein kinase C (PKC) in rat brain was demonstrated immunocytochemically by using polyclonal antibodies raised against a synthetic oligopeptide corresponding to the carboxyl-terminal sequence of a-PKC. The a-PKC-specific immunoreactivity was widely but discretely distributed in both gray and white matter. The immunoreactivity was associated predominantly with neurons, particularly with perikaryon, dendrite, or axon, but little was seen in the nucleus. (2), which correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
32
1

Year Published

1991
1991
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 34 publications
11
32
1
Order By: Relevance
“…The distribution of the PKC mRNA patterns are in good agreement with the patterns reported [4,8,19,31,34,35] and with the distribution of the PKC proteins as visualized by immunohistochemistry [8,19,31]. When the extinction values were corrected for differences in specific activity of the labeled oligonucleotides and differences of exposure duration, it was shown that the expression of the PKC isoforms is subject to a gene-specific and a regionally differential regulation.…”
Section: Discussionsupporting
confidence: 86%
“…The distribution of the PKC mRNA patterns are in good agreement with the patterns reported [4,8,19,31,34,35] and with the distribution of the PKC proteins as visualized by immunohistochemistry [8,19,31]. When the extinction values were corrected for differences in specific activity of the labeled oligonucleotides and differences of exposure duration, it was shown that the expression of the PKC isoforms is subject to a gene-specific and a regionally differential regulation.…”
Section: Discussionsupporting
confidence: 86%
“…In the present study, most of the PKC mRNAs were eventually de creased in the CAl area, most likely as a consequence of local neuronal degeneration. Because most of the PKC subspecies are expressed in the neurons (Huang et a!., 1988;Ito et a!., 1990), the decline in the expression of PKC isoforms after transient forebrain ischemia may be secondary to neuronal cell death. The remaining expression level of PKCa may therefore occur in either nonneuronal cells (Sieber et a!., 1998) or nonvulnerable CAl neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The rabbit antisera specific to the PKC subspecies were prepared against synthetic oligopepiides that correspond ;o the carboxvl-terminal nortion of each subsnecies (OFVHPILOSAV for the CX-PKC: SYTNPEI%INV for the PI-PK'C, and%VNSEFLKPEVKS for the BII-PKC, Hosoda et al, 1989;Saito et al, 1989;Ito et al, 1990). The monoclonal antibody to r-PKC, obtained by immunizing mice with the purified PKC from the soluble fraction of rat brain, was characterized (Hashimoto et al, 1988).…”
Section: Methodsmentioning
confidence: 99%
“…Among various tissues, the enzyme is most concentrated in the CNS (Minakuchi et al,198 1). Immunocytochemical and biochemical studies in this and other laboratories have revealed a differential regional and cellular localization of each PKC subspecies in the brain (Kitano et al, 1987;Hidaka et al, 1988;Huang et al, 1988;Kose et al, 1988;Saito et al, 1988Saito et al, , 1989Hosoda et al, 1989;Ito et al, 1990). Particularly, the r-PKC subspecies is found only in the CNS (Ohno et al, 1987).…”
mentioning
confidence: 99%